Isolation and characterization of actinobacteria with antibacterial and plant growth-promoting activities from maoberry cultivated soil in Northeast Thailand - Sangsila, A.; Pimda, W.; Jorjong, S.; Promden, W. (International Journal of Agricultural Technology, 2021)
A total of five actinomycetes were isolated from 20 soil samples collected after 12 months of paclobutrazol application at maoberry cultivation sites in Sakon Nakhon province, Northeast Thailand. The five actinomycetes isolates, namely SM-11, SM-31, SM-51, SM-52, and SM-53, were identified based on morphological characters, particularly pigment production, and then tested for antibacterial and plant growth-promoting activities. The results showed that the ethyl acetate and ethanolic extracts of the isolate SM-31 both exhibited excellent bacterial activities against Salmonella typhi and Staphylococcus aureus. Similar results were observed for the ethanolic extract of SM-31. Meanwhile, the isolates SM-11 and SM-31 displayed the best plant growth-promoting activities compared to the other isolates. Based on 16s rRNA gene and phylogenetic tree, the potential isolates belonged to Streptomyces (SM-11 and SM-31) and Amycolatopsis (SM-51) genera. The isolate SM-11 showed 99.66% similarity to Streptomyces roietensis strain WES2, Streptomyces xylanilyticus strain SR2-123 and Streptomyces mexicanus strain NBRC 100915. The isolate SM-31 displayed 99.83% similarity to S. tibetensis strain XZ 46, S. hawaiiensis strain ISP 5042, and S. coeruleofuscus strain CSSP429. Moreover, the isolate SM-51 is mostly related to Amycolatopsis rhabdoformis strain SB026 with 99.51% similarity. Overall, this study revealed that the selected actinobacteria recovered from maoberry cultivation sites served as a candidate to be explored as a source of bioactive compounds